2015
DOI: 10.1111/bph.13101
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of zofenoprilat as an inducer of functional angiogenesis through increased H2S availability

Abstract: Background and Purpose Hydrogen sulfide (H2S), an endogenous volatile mediator with pleiotropic functions, promotes vasorelaxation, exerts anti‐inflammatory actions and regulates angiogenesis. Previously, the SH‐containing angiotensin‐converting enzyme inhibitor (ACEI), zofenopril, was identified as being effective in preserving endothelial function and inducing angiogenesis among ACEIs. Based on the H2S donor property of its active metabolite zofenoprilat, the objective of this study was to evaluate whether z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 46 publications
1
37
0
Order By: Relevance
“…In a follow up study, Terzuoli et al reported that the zofenoprilat-induced angiogenic properties of endothelial cells were attenuated by CSE inhibition or silencing [94]. Similarly, PAG administration reduced neovascularization in the Matrigel® plug assay in vivo [94]. The molecular mechanisms underlying zofenopril-induced angiogenesis were dependent on Akt, eNOS and ERK1/2 cascades, in line with what is known about mediators of H 2 S-triggered angiogenic signaling.…”
Section: Pharmacological Agents That Promote Angiogenesis Through Endmentioning
confidence: 82%
See 1 more Smart Citation
“…In a follow up study, Terzuoli et al reported that the zofenoprilat-induced angiogenic properties of endothelial cells were attenuated by CSE inhibition or silencing [94]. Similarly, PAG administration reduced neovascularization in the Matrigel® plug assay in vivo [94]. The molecular mechanisms underlying zofenopril-induced angiogenesis were dependent on Akt, eNOS and ERK1/2 cascades, in line with what is known about mediators of H 2 S-triggered angiogenic signaling.…”
Section: Pharmacological Agents That Promote Angiogenesis Through Endmentioning
confidence: 82%
“…In a follow up study, Terzuoli et al reported that the zofenoprilat-induced angiogenic properties of endothelial cells were attenuated by CSE inhibition or silencing [94]. Similarly, PAG administration reduced neovascularization in the Matrigel® plug assay in vivo [94].…”
Section: Pharmacological Agents That Promote Angiogenesis Through Endmentioning
confidence: 99%
“…All experimental points using cells from the single culture plate were run in triplicate. After 2 days, cells were fixed, stained with H&E and randomly counted at 20× original magnification in 5 fields [19,20]. Data are reported as number of cells counted/well.…”
Section: Cell Survival and Proliferationmentioning
confidence: 99%
“…We have recently reported that ACEi dependent H 2 S exerts protective activity on ECs through activation of K ATP channel, PI-3 K and eNOS, as well as up-regulation of FGF-2 and telomerase, thus maintaining endothelial longevity and function [76][77][78]104] (Fig. 4).…”
Section: Nitric Oxide Donorsmentioning
confidence: 99%
“…Zofenoprilat induces a constant H 2 S production through CSE upregulation in vascular endothelium. On its turn H 2 S maintains ECs survival and stimulates the angiogenic process through a sequential pathway involving K ATP channel/Akt/ eNOS/ERK1/2 pathway (for details see [104]) studies evaluated the effectiveness of common antioxidants found in the diet, which are known to prevent cellular oxidative damage. Many animal models showed a reduction in anthracycline cardiotoxicity by coadministering compounds such as vitamin E, vitamin C, vitamin A, coenzyme Q, and flavonoids.…”
Section: Antioxidantsmentioning
confidence: 99%